2020
DOI: 10.1017/dmp.2020.378
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Preventive Behavior During the First 3 Months of the COVID-19 Outbreak in Iran

Abstract: Objectives: Iran is facing a big challenge controlling the COVID-19 outbreak and it is unclear to how individuals are engaging in preventive behaviors. This study aimed to investigate changes in preventive behaviors during the first three months of the COVID-19 outbreak in Iran. Method: This cross-sectional survey was conducted on 1477 adults aged 18years and older in 31 provinces of Iran. Data was collected by an anonymous online questionnaire. Result: Overall, engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Shiraly et al reported that wearing masks prevented touching mucosal zones of the face and infection transmission [41]. Shamsalinia et al reported that among Iranians, women and healthcare workers considered these behaviors excessive, and that all people accepted the rules against COVID-19 contraction only for the first two months [42]. Consistent with these results, the present study showed that among women, housewives were more involved with COVID-19 than other occupations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Shiraly et al reported that wearing masks prevented touching mucosal zones of the face and infection transmission [41]. Shamsalinia et al reported that among Iranians, women and healthcare workers considered these behaviors excessive, and that all people accepted the rules against COVID-19 contraction only for the first two months [42]. Consistent with these results, the present study showed that among women, housewives were more involved with COVID-19 than other occupations.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, being female was considered an effective factor in improving hand washing knowledge [43]. Several studies have shown that healthcare workers are more prone to contract COVID-19, and that there are more preventive strategies for them to be adopted [42,44,45]. Sabetian et al observed that in hospitals of the Fars Province, Iran, healthcare workers were more prone to contract COVID-19, with an incidence rate of 5.62% [45].…”
Section: Discussionmentioning
confidence: 85%
“…These actions, in combination with a community commitment to respect public health protocols, were highly useful during the first wave of the pandemic; as a result, after two months, the situation almost came under control, and the number of cases and hospitalization rates were decreased significantly. Unfortunately, due to relaxed restrictions that resulted in declined distancing (for instance, through holding ceremonies) and several other reasons, Iran soon faced the second wave of the COVID-19 pandemic (4). Scientists believe that evaluating clinical features, disease severity, outcomes, and other features during an epidemic can help health policymakers to make better decisions (5).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 affects people in several ways and symptoms of this virus are highly changeable and variable, ranging from none to severe disease. [ 4 ] A significant amount of infected patients will develop moderate-to-severe disease and recuperate with hospitalization. [ 5 ] Since COVID-19 initially emerged around the world, hospitals touched numerous challenges during such as severe shortages of health-care provider and difficulty in maintaining adequate staff, retaining institutional capacity, and lack of personal protective equipment as well as respiratory support materials and testing supplies.…”
Section: Introductionmentioning
confidence: 99%